ASSESSMENT OF REFLECTIVE LEARNING STRATEGIES IN PEDIATRIC SURGERY COURSE AT MEDICAL UNIVERSITY - Anatolii Levytskyi; Oxana Vygovska; Iryna Benzar; Dmytro Golovatiuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2021)
The article is aimed at studying medical students' reflective strategies for learning the Pediatric Surgery course at medical university. We used a modified version of the Motivated Strategies for Learning questionnaire (Soemantri et al., 2018), which has four subscales: self-orientation, critical thinking, self-regulation, and feedback seeking. The self-orientation component deals with students' perceptions on their self-efficacy and internal motivation. The participants were fourty-six 5-th year medical students from the Bogomolets National Medical University, Kyiv, Ukraine. The survey was held in May 2021 when the students finished their spring semester in the online mode. We observed the prevalence of high and moderate levels in all the variables, but the indicators of Feedback seeking are lower which can be explained by the specificities of online learning. The authors propose methodological recommendations for educators how to create an environment for reflective learning to develop students' reflective skills and employ alternative assessment strategies in the classroom.